Justification of calculation schemes choice for metalware segments of bridge crane trolleys based on multipurpose layout drawing configurations - Goncharov K.A.; Denisov I.A. (Научно-технический вестник Брянского государственного университета)
The article describes the choice features of the matrix elements of the calculation schemes of the metalware segments of the bridge crane trolleys on the basis of the multipurpose layout drawing in various design cases. The general sequence of the structure formation of the calculation scheme matrix is shown. The article proposes the analysis of the deformation mode of the standard load trolley metalware based on the multipurpose layout drawing when various loading cases occur. The stress distribution laws between the elements of the neighbouring metalware segments, depending on the characteristics of the arrangement of the loading forces, are determined. The implementation of the various types of the elementary calculations schemes, when performing analytical calculations of the metalware segments of the trolley, are justified, as well as the recommendations on the calculation scheme choice are given.